2018
DOI: 10.1093/ntr/nty241
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 Tips From Former Smokers® Campaign: Associations With Quit Intentions and Quit Attempts Among Smokers With and Without Mental Health Conditions

Abstract: Introduction People living with mental health conditions (MH+) are more likely to smoke cigarettes than people without mental health conditions (MH−) and to experience tobacco-related disparities. The Tips From Former Smokers® (Tips®) campaign is a proven population-level strategy for motivating smokers to quit. In 2016, Tips included ads featuring Rebecca, a former smoker with depression. We evaluated self-reported frequency of exposure to the Rebecca and other Tips ads in association with q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…The treatment includes combination NRT, and we are evaluating the nicotine metabolism ratio in predicting treatment outcome. To promote cessation in groups particularly vulnerable to tobacco use, emerging research has supported the value of targeted communication ( 185 ) and regulatory policies such as reducing nicotine levels in cigarettes ( 224 ), discussed next.…”
Section: Discussion: What Evidence Is Neededmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment includes combination NRT, and we are evaluating the nicotine metabolism ratio in predicting treatment outcome. To promote cessation in groups particularly vulnerable to tobacco use, emerging research has supported the value of targeted communication ( 185 ) and regulatory policies such as reducing nicotine levels in cigarettes ( 224 ), discussed next.…”
Section: Discussion: What Evidence Is Neededmentioning
confidence: 99%
“…In 2016, Tips ads featured Rebecca, a former smoker with depression. In a national evaluation, greater exposure to the Rebecca ads was associated with a greater likelihood of intending to quit and with making a quit attempt specifically among smokers with mental health conditions ( 185 ). National media campaigns are an important population-level strategy for reaching specific population groups, such as people living with mental health conditions, who are experiencing tobacco-related disparities.…”
Section: Tobacco Control Population-based and Policy Approachesmentioning
confidence: 99%
“…Advertising and mass media campaigns tailored for this population group may be an effective strategy for helping people with a mental health condition make positive changes to their lifestyle risk factors, warranting further research. For example, Prochaska and colleagues 41 found that exposure to advertisements focusing on an ex‐smoker with a mental health condition was associated with increased attempts to quit smoking among people with a mental health condition.…”
Section: Discussionmentioning
confidence: 99%
“…Underserved populations can be targeted by such national media campaigns, 13,16 resulting in enhanced quitline contacts by such populations. 17,18 Thus, the combination of barrierfree, easy-access, and targeted promotional activities likely accounts for quitlines' extraordinary reach into populations that are typically medically underserved; 50% or more of callers to the quitline are uninsured or receive Medicaid. 19,20 Quitlines' ubiquitous availability and absence of barriers allow them to serve multiple roles in tobacco use treatment, 21 including serving as important treatment extenders in healthcare settings.…”
Section: Quitlines Todaymentioning
confidence: 99%